Measuring and Comparing Cortical Surface Area of Paracentral Lobule in a Tertiary care Hospital, Bangladesh - Chowdhury, Mahfuza; Khatun, Monira; Rahman, Aminur; Kawsar , Tunajjina; Naznin, Rezowana; Rab, Ferdausi (Bangladesh Journal of Medicine, 2023)
Background: The paracentral lobule is the area on medial surface of the cerebral cortex which extends from precentral sulcus to postcentral sulcus. Any trauma, tumor, or cerebral ischemia cause lesions of motor and sensory cortex of paracentral lobule. The result of this study is very important to the radiologists and neurosurgeons for diagnosis of above mentioned diseases and the practice of safe neurosurgery. This study was carried out to observe the cortical surface area of paracentral lobule in adult male and female Bangladeshi population,may help for future research. Methods: This cross- sectional study was conducted in the Department of Anatomy, Dhaka Medical College, Dhaka, during the period of January 2017 to December 2017. Total 70 adult Bangladeshi male &female people were selected, among them 35 male and 35 female, age ranging from 20-65 years. CT scan image of brain in mid sagittal view was used for this study. Data were analyzed by Unpaired Student’s ‘t’ tests. Results: The surface area of motor cortex of right and left paracentral lobule was significantly higher (p<0.01) in male.Surface area of sensory cortex of both paracentral lobule was significantly higher (p<0.05) in male than female. Conclusion: The present study reveals significant difference in morphological measurements of right and left paracentral lobule between male and female of adult Bangladeshi population. Bangladesh J Medicine 2023; 34(3): 235-238